2018
DOI: 10.1007/s15010-018-1170-0
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide passive surveillance on fungal infections shows a low burden of azole resistance in molds and yeasts in Tyrol, Austria

Abstract: PurposeTo determine the burden of antifungal resistance in fungi over the last 10 years.MethodsPerformance of a semi-nationwide surveillance on antifungal resistance.ResultsWe observed a low frequency of azole resistance in Aspergillus fumigatus, a moderate increase of echinocandin resistance in yeasts, and a stable amphotericin B activity in yeasts and molds. Posaconazole resistance in Aspergillus terreus occurred in a few isolates.ConclusionThe burden of resistance in fungi seems to be low in Tyrol, Austria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Despite reports of azole resistance acquired after treatment, in common and rare yeast species, and description of an increasing percentage of resistant isolates (39), this phenomenon remains rare (1,16,40,41) or has geographical specificity (42,43), and seems to concern especially C. tropicalis, C. glabrata and C. parapsilosis (17). In the present study, we observed a proportion of fluconazole-resistant isolates among C. albicans and C. parapsilosis isolates similar to that reported in international surveys (17,19,20,28,44).…”
Section: Discussionsupporting
confidence: 83%
“…Despite reports of azole resistance acquired after treatment, in common and rare yeast species, and description of an increasing percentage of resistant isolates (39), this phenomenon remains rare (1,16,40,41) or has geographical specificity (42,43), and seems to concern especially C. tropicalis, C. glabrata and C. parapsilosis (17). In the present study, we observed a proportion of fluconazole-resistant isolates among C. albicans and C. parapsilosis isolates similar to that reported in international surveys (17,19,20,28,44).…”
Section: Discussionsupporting
confidence: 83%
“…Countries reporting the presence of azole-resistant Aspergillus fumigatus and mechanisms of resistance in surveyed isolates [47,48,49,52,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97]. …”
Section: Figurementioning
confidence: 99%
“…Aspergillus fumigatus , Aspergillus flavus and Aspergillus terreus exist ubiquitously in the environment. However, they are also important human pathogens causing allergic bronchopulmonary aspergillosis in patients with asthma or cystic fibrosis, chronic pulmonary aspergillosis in those with impaired lung tissue architecture and severe invasive infections in immunocompromised patients [ 1 , 2 , 3 ]. A. fumigatus is the most common cause of human Aspergillus infections globally, whereas the incidence of the other two species varies geographically.…”
Section: Introductionmentioning
confidence: 99%
“…A. fumigatus is the most common cause of human Aspergillus infections globally, whereas the incidence of the other two species varies geographically. A. flavus is the second most common species in Asia but A. terreus the second most common species in Austria [ 1 , 3 ]. A. fumigatus is known to be abundant in decaying vegetation in fields, forests, and compost heaps while both A. terreus and A. flavus are known to be abundant in soils [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%